2017
DOI: 10.15835/nbha45210877
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pollen Quality and Self-Fertility in Selected Cultivars of Asian and European Pears

Abstract: Asian pears have become increasingly popular in the European market, but their cultivation history in Europe is rather short. Pear is a demanding species in terms of pollen -donor cultivar. The self-fertility phenomenon in Asian pear cultivars is not currently known. The study was conducted in a 6-year pear orchard (of 23 Asian and 5 European cultivars) at the Mendel University in Lednice (Czech Republic). The following traits were assessed: number of pollen grains, pollen viability, pollen grain germination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Pollen germination in vitro varied from 2.6% ("Conference") to 71.3% ("Fritjof") in the first experimental year and from 11.5% ("Herzogin Elsa") to 88.0% ("Conference") in the second. Those data go are in line with the results obtained by Shafari [35], who studied pear cultivars from the East Azerbaijan Province of Iran and Bhat et al [36] and Bieniasz et al [37], who both studied Asian and European pear cultivars. The germination test in vitro showed that almost all pollinizers had higher pollen germination in the second year.…”
Section: Pollen Germination In Vitrosupporting
confidence: 91%
“…Pollen germination in vitro varied from 2.6% ("Conference") to 71.3% ("Fritjof") in the first experimental year and from 11.5% ("Herzogin Elsa") to 88.0% ("Conference") in the second. Those data go are in line with the results obtained by Shafari [35], who studied pear cultivars from the East Azerbaijan Province of Iran and Bhat et al [36] and Bieniasz et al [37], who both studied Asian and European pear cultivars. The germination test in vitro showed that almost all pollinizers had higher pollen germination in the second year.…”
Section: Pollen Germination In Vitrosupporting
confidence: 91%
“…In Belgium, 'Comice' or 'Triomphe de Vienne' are recommended in Conference orchards to achieve good yields (Warnier 2000). Other recommended cultivars for Conference include Williams, Concorde and Passe Crassane (Moriya et al 2005), and recently several studies have shown that Asian pear varieties can fertilize Conference (Quinet et al 2016a;Bieniasz et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that viable and compatible pollen grains adhere to receptive stigma, whereas incompatible or ones which fall on the unreceptive stigma are washed away by rain. Such observations were made by many authors with regard to other fruit species [29,35,36]. Combinations, where the number of pollen grains on the stigma rated 3 or 2 on our scale, should be classified as compatible with a high amount of germinating pollen grains.…”
Section: Discussionmentioning
confidence: 58%